Community Perception Regarding Socio-Economic Causes of Increasing Divorce among Females: A Sociological Study in District Muzaffar Garh - Nadia Akhtar; Dr. Muhammad Ali Tarar; Sumaira Bano; Sharjeel Saleem; Ayesha Anwar; Anam Zahra (Research Journal of Psychology, 2024)
Marriage and separation are societal problems as well as reserved distresses. Divorce is a lifetime stressor for an individual, complicated with theoretically harmful values for the emotional and physical fitness of all fellows of the household. The simple determination of this assessment is to deliver detailed information around the influence of separation on peoples’ lifespan. The objectives of study were i) to study the socio-economic characteristics of the respondents, ii) to investigate the socio-economic causes of increasing divorce among females, iii) to study the perceived adverse effects of parent's divorce on the children, and iv) to suggest some measures how to minimize the divorce rate in community and its negative effects on the children. This research was investigated in District Muzafar Garh, in South Punjab & 180 community peoples were selected from 1 selected tehsil through multistage sampling technique. The results indicated that majority of participants (51.1%) were females, their age ranges from 40 to upto 53 years old (60.0%), were married (87.7%), had been completed upto matriculation level (56.1%), and their spousal education was upto matriculation level (58.9%). A mixed results were found majority (55.0%) were housewives, and daily wage labourers, are belonged to lives in nuclear family system, and their family income ranges from 20,000 to upto 50,000 rupees in per month (62.8%). The results investigated the socio-economic causes of increasing divorce among females i.e. majority (68.9%) said that divorce rate is increasing among females day by day in society to some extent. A significance proportion of participants (90.0%) were agreed domestic violence is a cause of increasing divorce among females, societal pressure contributes to the rising divorce (47.2%), problems with in-laws (51.1%), lack of communication skills leads to higher divorce (48.3%), extra-marital affair of husband (92.8%), female infertility status (95.0%) and agreed with the statement husband’s impotence is a cause of divorce among females (86.6%). The results were found economic causes i.e. majority (89.5%) of participants were agreed financial instability is a leading cause of divorce among females, unequal financial contributions pressure marriages (86.7%), unemployment leads to marital stress and divorce (91.7%), financial disagreements factors (91.7%), financial instability due to factors like job loss (85.6%), financial independence (83.3%) and one-third (36.7%) of the respondents were agreed that husband’s low income to meet household needs is a cause of divorce among females. According to this objective to study the perceived adverse effects of parent’s divorce on the children, the results showed that majority (89.5%) of respondents were agreed children of divorced parents suffer from emotional distress, parental divorce negatively impacts children’s academic performance (91.7%), parental divorce leads to behavioural problems in children (91.7%), children of divorced parents often feel neglected (89.4%), children of divorced parents struggle with trust issues (70.0%) and a huge majority (63.9%) of participants were agreed that divorce contributed feelings of inferiority in children. The study was concluded that the hypothesis testing showed there was a positive relationship between lesser the spousal education and divorce increased among females in society (χ2 = 19.841, probability = 0.031). There was a positive association between divorce increased among females in society and community people hates the divorcee female (χ2 = 33.749, probability = 0.000). The result of these assumptions showed extra-marital affairs of husband (χ2 = 15.845, probability = 0.045), husband’s impotence (χ2 = 32.272, probability = 0.000) and unemployment leads to marital stress (χ2 = 19.841, probability = 0.031) cause of divorce among females in society. So, all these hypotheses are significant and accepted.